2019
DOI: 10.3892/ol.2019.10557
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma grading and recurrence prediction using T1 mapping on gadolinium‑ethoxybenzyl diethylenetriamine pentaacetic acid‑enhanced magnetic resonance imaging

Abstract: The aim of the present study was to explore the value of T 1 mapping on gadolinium-ethoxybenzyl diethylenetriamine pentaacetic (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (MRI) for grading hepatocellular carcinoma (HCC) and predicting its recurrence rate. A retrospective study was performed that included 75 patients (66 men and 9 women; mean age, 52.89 years; age range, 23–79 years) with HCC who had undergone Gd-EOB-DTPA-enhanced MRI with T 1 mapping before s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…As opposed to most previous studies in which patients were classified into two subgroups (low and high risk) according to their risk of recurrence [ 7 , 9 , 10 , 18 – 22 ], herein, we identified a fraction of medium-risk patients by stratifying LR-5 HCC patients into three subcategories with significantly different early recurrence rate and disease-free survival. Although Qin X et al stratified HCC patients into three subgroups with low, medium, and high recurrence rate by using the parameters of T1 mapping, the recurrence rates were not significantly different between subgroups of high- and medium-risk of recurrence in that study [ 23 ]. In addition, our method only requires counting the number of the risk factors, with complicated equations or calculations uninvolved, which enables clinicians to estimate the risk stratification quickly and discuss with patients efficiently before treatment.…”
Section: Discussionmentioning
confidence: 97%
“…As opposed to most previous studies in which patients were classified into two subgroups (low and high risk) according to their risk of recurrence [ 7 , 9 , 10 , 18 – 22 ], herein, we identified a fraction of medium-risk patients by stratifying LR-5 HCC patients into three subcategories with significantly different early recurrence rate and disease-free survival. Although Qin X et al stratified HCC patients into three subgroups with low, medium, and high recurrence rate by using the parameters of T1 mapping, the recurrence rates were not significantly different between subgroups of high- and medium-risk of recurrence in that study [ 23 ]. In addition, our method only requires counting the number of the risk factors, with complicated equations or calculations uninvolved, which enables clinicians to estimate the risk stratification quickly and discuss with patients efficiently before treatment.…”
Section: Discussionmentioning
confidence: 97%
“…More importantly, the decline of OATP expression precedes the typical vascular changes of hepatocarcinogenesis, making the hypo-intensity on the hepatobiliary phase the most sensitive imaging feature for early diagnosis of HCC [ 125 , 126 , 130 , 154 , 155 ]. Typical HCC appears hypo-intense on the hepatobiliary phase and the degree of hypo-intensity has been correlated to histologic grading [ 156 ] [ 157 , 158 ]; however, approximately 10% of HCCs appear iso-intense or hyperintense relative to the surrounding liver on the hepatobiliary phase with gadoxetate (paradoxical uptake). The iso/hyperintensity may not be due to tumor differentiation, but rather represents a peculiar molecular/genetic subtype—probably due to genetic or epigenetic alterations—with less aggressive biological features [ 159 , 160 ].…”
Section: Mrimentioning
confidence: 99%
“…Also, T1 mapping can be integrated seamlessly into gadoxetic acid-enhanced MRI to provide high temporal and spatial resolution images with the precontrast, postcontrast T1 relaxation time and its reduction rate (Δ %) calculated. Some previous studies have demonstrated that the parameters of T1 mapping were helpful for predicting histologic grades and recurrence after resection of HCC [19][20][21].…”
Section: Introductionmentioning
confidence: 99%